2015
DOI: 10.1080/1369183x.2015.1015408
|View full text |Cite
|
Sign up to set email alerts
|

Between Security and Mobility: Negotiating a Hardening Border Regime in the Russian-Estonian Borderland

Abstract: Since the end of the Cold War order post-Soviet borders have been characterised by geopolitical tensions and divergent imaginations of desirable political and spatial orders. Drawing upon ethnographic research in two border towns at the Russian-Estonian border, the article makes a case for a grounded examination of these border dynamics that takes into account how borders as sites of 'mobility and enclosure' are negotiated in everyday life and shaped by the differentiated incorporations of statecraft into peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“…It is with regret that we have not been able to cover Moldova, an under-researched country with a large Russian-speaking population and its own particular internal dynamics. (Pfoser 2015) has shown how even the political border with Russia is more securitised in Latvian and Estonian political discourse than in the everyday practices of the people who dwell in these regions. Likewise, numerous authors have reported how lived experiences and interactions in the Baltic states are far less ethnicised and rigidly demarked than the political rhetoric suggests (Cheskin 2016, pp.…”
Section: Latvia and Estoniamentioning
confidence: 99%
“…It is with regret that we have not been able to cover Moldova, an under-researched country with a large Russian-speaking population and its own particular internal dynamics. (Pfoser 2015) has shown how even the political border with Russia is more securitised in Latvian and Estonian political discourse than in the everyday practices of the people who dwell in these regions. Likewise, numerous authors have reported how lived experiences and interactions in the Baltic states are far less ethnicised and rigidly demarked than the political rhetoric suggests (Cheskin 2016, pp.…”
Section: Latvia and Estoniamentioning
confidence: 99%
“…Discourses on migration by residents of Narva amply demonstrate how the identity-driven narratives on ethnic minorities re-articulate the rhetoric of political exclusion as triggered by the refugee crisis. The Estonian city of Narva and the adjacent region of Ida-Virumaa are widely considered as a Russian-language enclave with the population characterized by the Sovietstyle mentality, which is culturally and politically remote from the dominant Estonian majority (Kallas 2016;Kattago 2008;Pfoser 2015;Trimbach and Shannon 2015;Zabrodskaja 2015). Many popular and academic works portray the Ida-Virumaa region and Narva as sources of a peculiar identity, which is very different from other Estonian lands (Khvostov 2013;Raik 2014).…”
Section: Contextualizing Estonia Against the Backdrop Of The Refugee mentioning
confidence: 99%
“…En este modelo, la regulación de la movilidad adquiere una importancia particular (Pfoser, 2015). Como se indicó, dado que el espacio más allá de las fronteras se concibe como fuente de amenazas potenciales, la "violación" de la frontera se considera una agresión contra el Estado.…”
Section: Una Visión Embrionaria: Las Fronteras Como Líneas Que Dividenunclassified
“…Sin embargo, en los últimos años se han hecho evidentes las limitaciones de esa visión de las fronteras, pues deriva en una comprensión restringida de su funcionamiento y sus significados (Pfoser, 2015). Un primer aspecto problemático consiste en que se naturalizan muchos elementos que en realidad se construyen socialmente.…”
Section: Una Visión Embrionaria: Las Fronteras Como Líneas Que Dividenunclassified